IMPLEMENTASI DIGITALISASI INFORMASI SEKOLAH TK MELALUI PEMBUATAN WEBSITE - Asep Kurnia Jayadinata; Hisaanah, Isti Maimuun; Mutia Rachmadilla; Pradnya Syaira Fatanaya; Reisa Puji Rosalvaluna; Risma Parwati; Tria Rizky Gantika; Cucun Yunianingsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The development of information technology has had a significant impact on the world of early childhood education. However, the current problem is that many early childhood education institutions still use conventional communication methods, limiting access to information for parents, as is the case at TK Plus Roudhoh Purwakarta. Based on this background, digital media is needed to facilitate access to information. This study aims to describe the process of implementing information digitization through the creation of a school website at TK Plus Roudhoh Purwakarta. The research method used is a qualitative descriptive study, beginning with the pre-field stage, namely collecting initial information about the school's condition using data collection techniques such as observation, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusions. The results of the study showed that training and mentoring on website creation for kindergarten teachers successfully had a positive impact on managing the school website independently, including updating content and information regularly. The developed website serves as a medium for information dissemination, school promotion, communication with parents, and documentation of activities. This implementation has had a positive impact on the effectiveness of school communication, increasing digital teacher literacy, and facilitating information access for the community. This study concludes that website creation is the first step in supporting the digital transformation of schools and improving the quality of information services.